Pemilihan Kepala Daerah di Indonesia Setelah Reformasi: Kesinambungan dan Perubahan - Muhammad Bahrul Ulum (Undang: Jurnal Hukum, 2021)
Election becomes the main feature of liberal democracy and a prerequisite of the working of democracy. After Indonesia’s reformation, an election has played an important role in engaging citizens to participate in the government. It includes the subsequent introduction of elections at the local level that portrays an increasing role of citizens in democracy at the grassroots. Consequently, every position of the regional head, both at the provincial and district/city levels, should involve citizens’ direct intervention to implement “the regional head to be democratically elected”, the norm outlined in Article 18 (4) of the 1945 Constitution. This paper aims to trace the historical trajectory and development of the direct regional head election and analyze the extent to which its continuities and changes in the last two decades have linkages to the performance of Indonesian democracy. By examining the relevance of regional head elections to Indonesia’s contemporary democracy after two decades of reform, this paper specifically reflects on the interpretation of the above constitutional norm through regional head elections, which in practice become problematic because money politics is often unavoidable. This money politics in this local election encourages the regression of the Indonesian democracy because direct regional head elections do not necessarily reduce vote manipulation as had been practiced in regional head votings by members of the Regional People’s Representative Council. Abstrak Pemilu menjadi substansi utama dalam demokrasi liberal dan merupakan prasyarat berfungsinya demokrasi. Setelah reformasi Indonesia, pemilu berperan penting dengan melibatkan warga untuk berpartisipasi dalam pemerintahan, yang kemudian mencakup dikenalkannya pemilihan tingkat lokal sebagai peningkatan peran warga negara dalam demokrasi di akar rumput. Oleh karena itu, setiap jabatan kepala daerah, baik di tingkat provinsi maupun kabupaten/kota, harus melibatkan intervensi langsung warga negara untuk melaksanakan “kepala daerah dipilih secara demokratis”, norma yang dituangkan dalam Pasal 18 ayat (4) UUD 1945. Tulisan ini bertujuan untuk menelusuri lintasan sejarah dan perkembangan pemilihan kepala daerah langsung serta menganalisis sejauh mana kesinambungan dan perubahannya dalam dua dekade terakhir memiliki keterkaitan dengan kinerja demokrasi Indonesia. Dengan mengkaji relevansi pemilihan kepala daerah terhadap demokrasi kontemporer Indonesia setelah dua dekade reformasi, tulisan ini secara khusus merefleksikan interpretasi norma konstitusi di atas melalui pemilihan kepala daerah yang dalam praktiknya menjadi problematik karena sering tidak dapat terhindarkan dari politik uang. Politik uang dalam pemilihan kepala daerah ini mendorong regresi demokrasi di Indonesia karena pemilihan secara langsung tidak serta merta dapat mengurangi praktik manipulasi suara sebagaimana yang pernah dipraktikkan dalam pemilihan kepala daerah oleh anggota Dewan Perwakilan Rakyat Daerah.